Types of ethical conflict and management forms in social education and social work. Challenges in training politics - Vilar Martín, Jesús; Riberas Bargalló, Gisela (Education Policy Analysis Archives, 2017)
This paper presents the results of an investigation that analyses two important and interrelated issues: firstly, what are the main types of ethical conflict that social education and social work professionals experiment with; and secondly, which are the most prevalent management forms. From the data obtained, the elements that determine the way the professionals tackle value conflicts are identified, and criterion are suggested in order to implement more effective training policies to approach situations of complexity, as in the case of value conflict.